(untitled) (International Journal of Engineering and Computer Science, 2017)
In this era of internet, web sites are increasing tremendously in its volume and also becoming complex. Web Usage mining is the application of different data mining techniques on the web data which tracks user’s navigational behaviors using their history of records and extracts the information of user interest using patterns. The obtained results are used in different applications such as recommender systems, business intelligence and site improvement. This paper emphasizes on the idea of better understanding of user’s profile and site objectives, as well as the way users will browse web pages to better serve them withlist of web pages which are relevant to him by comparing with user’s historic pattern using different web usage mining techniques.This paper also discusses different applications of Web usage mining.